Principles and practices for the safe processing of foods (Woodhead Publishing, 1998)
This basic food industry handbook provides food processing managers, engineers and sanitarians with a practical, science-based guide to food safety in the context of food processing operations. All significant aspects are covered in detail, including building design and materials, plant layout and sanitation, safety aspects of processing methods, and safety management of ingredients and products.